ANALISIS DAN PERANCANGAN SISTEM INFORMASI SIMULASI PENGECATAN KENDARAAN BERBASIS ANDROID - Rian Yussandi (Universitas Teknokrat Indonesia, 2021)
Android is a mobile device on the operating system for mobile phones based on Linux, android provides an open platform for developers to create applications. Android-based application developers make applications so that they can be useful for the community ranging from game genre applications, education, entertainment and simulation applications that are very likely to be created and run on this android operating system. Simulation is the process of designing a matemastis or logical model of a real system, conducting experiments on models using computers to describe, explain and predict system behavior. For a simulation application company can be used as a medium of product promotion, while for smartphone users can help to channel the existing imagination into a real picture. The application of simulation applications many functions, one example of its application to two-wheeled motor vehicles. By utilizing android application and the growth of vehicle users that lead to the hobby of modification, it can be utilized by creating an android-based coloring simulation application to help modifiers and modification lovers in order to channel their imagination and make it easier to design colors as desired. Without having to bother using design software that requires special skills